Factors Influencing ICT Accessibility among the Farming Community of Odisha - Satapathy, Guru Prasad; Das, Sarbani; Tripathy, Maitreyee (Indian Journal of Extension Education, 2024)
In the dynamic agrarian landscape, Information and Communication Technologies (ICTs) herald a transformative era for agricultural services, providing a realistic and efficient platform essential for adapting to constant change and optimizing agricultural productivity. A study was conducted in the year 2023 to delineate the accessibility of ICTs in two purposively selected districts of Odisha, having the highest numbers of farmers using ICTs i.e. Khurda and Bargarh, constituting randomly selected 200 respondents. The study categorizes accessibility of ICTs among farmers into high (30%), medium (41.5%), and low (28.5%) levels. The significant predictors were ICT accessibility, with educational qualification (b = 0.133, p < 0.01), annual income (b = 0.068, p < 0.01), social participation (b = 0.0341, p < 0.01), and media exposure (b = 0.478, p < 0.01) exhibiting positive regression coefficients. Conversely, age (b = -0.888, p < 0.01) demonstrated a negative association with ICT accessibility. By prioritizing equitable access to resources and tailored interventions, policymakers and development practitioners can contribute to inclusive agricultural development and digital empowerment in Odisha, thereby fostering sustainable growth and resilience in the agricultural sector.
Keywords: Community; Factor; Farming; ICT accessibility; Influencing; Odisha